MODEL GALLERY WALK PADA PEMBELAJARAN AKUNTANSI MATERI JURNAL KHUSUS PERUSAHAAN DAGANG - Sigit Marteja (Jurnal Perspektif Pendidikan, 2020)
The problem in this research is the low learning activity of students in accounting subject matter in specialized journals of trading companies. The obstacle experienced by students is the lack of student learning enthusiasm. Both classical and group learning processes are not yet pleasant for students. Alternative problem solving is through the Gallery Walk model. The purpose of this research is to find out how Gallery Walk model learning can encourage students to learn about specialized journals of trading companies more enthusiastically. Data collection uses observation, questionnaires, written tests and deeds. The study was conducted by the classroom action research (CAR) method. subjects 24 high school students 1 Rejang Lebong class XII IPS 2. Data collection techniques using test and observation techniques. Quantitative and qualitative analysis techniques. Research results (1) In the first cycle, group learning activities of the first cycle reached 79.55% , the second cycle reached 84.71%, and the third cycle reached 97.32%. This increase shows an increase in group learning activities in participating in learning accounting for the Special Trading Company Journal. (2) Classical learning from cycle I reached 55.83%, cycle II reached 68.33%, and cycle III reached 97.48%. The increase shows an increase in students' enthusiasm for learning in accounting material Journal specifically Gallery Walk learning model an increase in active students from cycle 1, cycle 2 and cycle 3. Increased average learning outcomes followed by mastery learning. Cycle I achieved an average of 59.16 and students completing learning 45.83%, Cycle II achieved an average of 67.08 and students completing learning 54.16%, Cycle III achieved an average of 85.41 and students completing learning 100%, Because mastery learning has been reaching 100% scored> 70-75 then the specified target has been achieved. Based on the results of the study it can be concluded (1) Learning Gallery Walk model can increase learning activities more excited both classical, group and individual.The